Prediction of weaning readiness off nasal CPAP in preterm infants using point‐of‐care lung ultrasound. Issue 9 (13th June 2022) - Abdelmawla, Mohamed; Seleem, Wail; Farooqui, Mansoor; Eltayeb, Abdulla; Elsayed, Yasser
Abstract: This study's primary aim was to assess whether end‐expiratory lung ultrasound severity score (expLUSsc) at Day 3 of life, the second week of life, and before weaning off nasal continuous positive airway pressure (nCPAP) can predict the weaning readiness off nCPAP trial in preterm infants. The secondary aim was to evaluate the value of adding lung tidal recruitment (LTR) to expLUSsc (expLUSsc‐plus‐LTR) to improve predictability. We conducted a prospective study on premature infants <33 weeks of gestation. Point‐of‐care lung ultrasound (POC‐LUS) was performed on Day 3, the second week of life, before and after the trial off nCPAP. expLUSsc, pleural thickness, and LTR were assessed. A receiver operator curve was constructed to evaluate the ability of POC‐LUS to predict the weaning readiness off nCPAP. A total of 148 studies were performed on 39 infants, of them 12 weaned off nCPAP from the first trial and 27 infants failed attempts off nCPAP. An expLUSsc cut‐off 8 before the first trial of weaning off nCPAP has a sensitivity and specificity of 88% and 90%, and positive and negative predictive values of 87% and 92%, respectively, with area under the curve (AUC) was 0.87 (CI: 0.8–0.93), p < .0001. If LTR is added to an expLUSsc cut‐off 8 (expLUSsc‐plus‐LTR) before the first trial of weaning, then sensitivity and specificity of 95% and 90%, and positive and negative predictive values of 88% and 90%, respectively, with AUC was 0.95 (CI: 0.91–0.99), p < .0001. In conclusion, this study demonstrated the ability of POC‐LUS to predict the weaning readiness off nCPAP in premature infants. The use of this simple bedside noninvasive test can potentially avoid the exposure of premature infants to multiple unsuccessful weaning cycles.